Factors associated with sexual harassment of women in hospitality workplaces in Bahir dar, Ethiopia - Mulugeta Dile Worke; Zewdie Birhanu Koricha; Gurmesa Tura Debelew (Scientific Reports)
Abstract Sexual harassment in the workplace is a pervasive issue that disproportionately affects women and is linked to poor physical and mental health outcomes. Women employed in insecure and irregular job sectors, such as hospitality, are particularly vulnerable due to precarious working conditions and power imbalances. Despite its significance, there is limited empirical evidence on the prevalence, characteristics, and determinants of workplace sexual harassment in Ethiopia, hampering the development of effective intervention strategies. Thus, this study determined the prevalence and identified the organizational and individual-level factors that influence the experience of workplace sexual harassment in Bahir Dar city, Ethiopia. A cross-sectional survey was conducted among 50 hospitality workers, achieving a response rate of 100% and ensuring a representative sample of the target population. Data were collected using structured interviews and self-administered questionnaires to capture individual, workplace, and societal factors influencing sexual harassment. The Kobo toolbox was used to collect data. Linear mixed-effects modeling was employed to analyze the hierarchical nature of the data, accounting for variations at multiple levels, including individual worker characteristics, workplace environments, and broader socio-cultural dynamics. Fixed effects were expressed as β-coefficients with 95% confidence intervals. The statistical significance of the findings was determined with a p-value < 0.05. The findings reveal that 81.5% of women employees experienced sexual harassment, with managers perpetrating 60.5% of the harassment against women. Factors such as perception and neuroticism were the individual-level characteristics positively associated with the sexual harassment experience, and having a college diploma or above had a negative association. Similarly, gender ratio, precarious employment, and working in a hotel were the organizational-level variables positively associated with sexual harassment experience. This study offers novel empirical evidence on workplace sexual harassment in Ethiopia, contributing to academic discourse and policy development. Using linear mixed-effects modeling strengthens the study’s analytical depth by capturing multi-level influences often overlooked in previous research. Policymakers and employers must prioritize comprehensive workplace interventions that address structural vulnerabilities and foster safer, more inclusive work environments.